Legal Consequences of Bankruptcy Towards Legal Position of Waqf Assets on Foundation - Sbong Sinarok Martin (Jurnal Hukum Novelty, 2021)
Introduction to the Problem: Based on Law No. 37 of 2004 on the Bankruptcy and Payment Suspension, the consequence of Bankruptcy decisions cover the total wealth of the Bankrupt Debtors at the time of the bankruptcy declaration together with that which they acquire during the bankruptcy. According to the Bankruptcy Act, there is no explicit limitation about the bankrupt assets, which raises the ambiguity and contradiction towards the Law No. 41 of 2004 on Waqf and Law No. 28 of 2004 on the amendment of Law No. 16 of 2001 on Foundations in determining the status of waqf assets as the one of Foundation’s wealth.Purpose/Objective Study: This research aims to determine waqf assets’ status on the bankrupt foundation and manage waqf assets in Indonesia’s bankruptcy proceedings.Design/Methodology/Approach: This type of research is normative legal research. The study employed secondary data from the literature review and analyzed it through the statute and conceptual approaches.Findings: This research shows that applying the laws and implementing bankruptcy proceedings should consider other laws, which means waqf assets that the foundation manages. The waqf law overrides the bankruptcy law that is affirmed on foundation law. The bankrupt foundation’s waqf assets will hand over to others’ foundations or legal entities that have the same purposes.Paper Type: Research Article.